2021
DOI: 10.1038/s41598-021-91097-3
|View full text |Cite
|
Sign up to set email alerts
|

Roughness of retinal layers in Alzheimer’s disease

Abstract: There is growing evidence that thinned retinal regions are interspersed with thickened regions in all retinal layers of patients with Alzheimer’s disease (AD), causing roughness to appear on layer thickness maps. The hypothesis is that roughness of retinal layers, assessed by the fractal dimension (FD) of their thickness maps, is an early biomarker of AD. Ten retinal layers have been studied in macular volumes of optical coherence tomography from 24 healthy volunteers and 19 patients with mild AD (Mini-Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the outcomes of [69] indicated a significant thinning of macular RNFL (mRNFL), GCL, IPL, and ONL for AD contrasted with HCs. The results in [42] align with those in [47], indicating that a pronounced thinning of macular layers mRNFL, INL, and OSL is related to mild AD rather than to HCs. Although both works by [92] and [42] agreed that a noteworthy thinning of GCL and IPL layers is associated with mild AD unlike HCs; however, the findings of [47] is conflicting such that the thickness changes of both GCL and IPL layers were insignificant between both groups.…”
Section: Macula-related Parameterssupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, the outcomes of [69] indicated a significant thinning of macular RNFL (mRNFL), GCL, IPL, and ONL for AD contrasted with HCs. The results in [42] align with those in [47], indicating that a pronounced thinning of macular layers mRNFL, INL, and OSL is related to mild AD rather than to HCs. Although both works by [92] and [42] agreed that a noteworthy thinning of GCL and IPL layers is associated with mild AD unlike HCs; however, the findings of [47] is conflicting such that the thickness changes of both GCL and IPL layers were insignificant between both groups.…”
Section: Macula-related Parameterssupporting
confidence: 71%
“…The results in [42] align with those in [47], indicating that a pronounced thinning of macular layers mRNFL, INL, and OSL is related to mild AD rather than to HCs. Although both works by [92] and [42] agreed that a noteworthy thinning of GCL and IPL layers is associated with mild AD unlike HCs; however, the findings of [47] is conflicting such that the thickness changes of both GCL and IPL layers were insignificant between both groups. The results reported in [17] agreed with [33] such that a notable thickness reduction of GCC layer is associated with MCI or aMCI rather than HCs.…”
Section: Macula-related Parameterssupporting
confidence: 71%
See 1 more Smart Citation
“…This is consistent across all types of OCT devices. Our findings indicate that thinning of the RNFL and pRNFL may be associated with poorer cognitive function, however, within the last decade, studies have found more varied results for pRNFL, with only 6 (out of 21, 28.6%) studies identifying an association 13 26–30. On the other hand, 45.5% of studies using OCT devices to measure RNFL thickness have identified a positive correlation with cognitive impairment, although studies with larger sample sizes (eg, Sánchez et al ,31 930; van de Kreeke et al ,32 298) found no significant correlation.…”
Section: Discussionmentioning
confidence: 67%